Redeveloping Newcastle : public incentives to spur commercial development - Furfine, Craig (London : Kellogg School of Management, 2016)
Louise Dejan was a successful real estate developer operating throughout northeast England. The city council of her hometown of Newcastle faced a problem common to many areas: how to encourage private investment into less attractive areas. In August 2012, Newcastle's East Pilgrim Street neighborhood remained an eyesore, despite its great location between the city's Central Station and city hall. It was a natural place for Dejan to build a typical urban office building over street-level retail building. On a particularly attractive site sat an asbestos-contaminated building, which was a former home to the Bank of England. The costs of remediation had kept developers like Dejan away for many years. To encourage redevelopment, the Newcastle City Council had recently designated the East Pilgrim Street neighborhood an Accelerated Development Zone (ADZ). This gave Dejan access to Tax Increment Financing (TIF), a method by which public funds could be spent to encourage private sector redevelopment of designated parcels of land. After studying the details of TIF and the financial projections of a potential new development, Dejan had to decide whether she should be the first to redevelop property in this well-located but seemingly forgotten neighborhood.
Originally published in Furfine, C. (2016). Redeveloping Newcastle: Public incentives to spur commercial development. 5-315-506. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Dejan, Louise; Bank of England. -- Asset Purchase Facility Fund; Urban renewal -- England